Flower differentiation, pollination and syncarp development of jackfruit cv. Tekam Yellow - Mijin, Salumiah (2019)
Irregular shape and size of syncarp are common problems in jackfruit production. Poor pollination may be the cause where syncarp does not reflect its varietal characteristics of a jackfruit variety. Varietal characteristic is closely linked with grade standard of a fruit. Besides, farmers are still using their empirical experiences in harvesting the syncarp for various destinations of markets. Maturity at harvest is an important factor that dictates fruit quality. Since these pieces of information are lacking in jackfruit, a systematic study starting from floral biology, followed by syncarp development and bulb quality were carried out. This study was conducted at a jackfruit commercial farm in Bukit Beruntung, Selangor. Inflorescences of male and female were tagged and monitored for their development. For assisted pollination, the selected female inflorescences were covered with bags before anthesis. Hand pollination was carried out by gently rubbing matured male inflorescences over the surface of the receptive female inflorescences. For natural pollination, female inflorescences were left to develop by themselves. Syncarp characteristics and physico-chemical changes during growth and development were determined. Jackfruit is a monoecious tree and both male and female inflorescences are found on the same tree. Generally, the male inflorescence of jackfruit cv. Tekam Yellow fell off starting from day 36 to 53 after emergence with mould covering its surface. During anthesis, the surface of male inflorescence was densely covered with yellow coloured anthers. Once anther dehisced, the pollen grains were released from anther over a mean period of three days before the empty pollen sac wilted and abscised. However, female inflorescence took 92 to 130 days after emergence to mature with stigmatic receptivity can be identified by fleshy, straight and milky-white stigmas. The shape of stigma is spathulate or ligulate and slightly curved. The receptivity of a stigma lasted about 5 to 7 days and after anthesis, stigma started to wither and bend with hyphae growing on its surface. The syncarp of jackfruit took 13 weeks after anthesis (WAA) before its growth curve reached plateau. The assisted pollination syncarp has perfect shape, heavier weight and higher bulb percentage with thicker bulb compared to naturally pollinated syncarp. Pollination techniques were found to affect the development, shape and eating quality of a jackfruit. Glucose, fructose and sucrose were significantly higher in ripen bulb than unripen. The ripe bulb of jackfruit also contained higher amount of phenolic acids and thereby, signified the importance of nutritional value for human health. Jackruit syncarp harvested at 14 WAA was higher in soluble solid content (SSC) than those harvested at 12 WAA. Similarly, jackfruit harvested at 14 and 15 WAA was higher in β-carotene content than those harvested at 12 WAA. In conclusion, it is recommended that the optimum harvesting stage of jackfruit cv. Tekam Yellow is 14 WAA for local market and 12 WAA for export.